Early Post-Stroke Seizures: A Comparison Between Acute Ischemic and Haemorrhagic Stroke Patients - Khan, Imran; Khan, Zubair Waheed; Khattak, Abdul Latif; Anwar, Javed; Ibrahim, Tahir; Hassan, Fayyaz (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the frequency of post-stroke seizure between acute ischemic and haemorrhagic stroke patients. Study Design: Comparative, prospective study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Oct 2021 to Oct 2022. Methodology: A total of 180 patients with acute stroke, were included in the study. CT brain and/or MRI brain were performed to diagnose all patients. Patients were divided into haemorrhagic and ischemic stroke groups. Patients were followed for four weeks. Results: The mean age of the patients was 48.92±7.80 years. The majority were males 127(70.5%),125(69.4%) patients had an ischemic stroke, while 55(30.6%) had haemorrhagic. Post-stroke seizures were seen in 12(7.07%). In haemorrhagic stroke patients, the frequency was 5/55(9.09%), while 7/125(5.6%) in ischemic ones. The difference in frequencies was 4.03%. There was no significant difference in seizure frequencies between the two groups (p=0.298). Conclusion: This study concluded that there is no significant statistical difference in frequencies of post-stroke seizure in haemorrhagic stroke compared to ischemic stroke patients.